Big data, artificial intelligence and biosecurity on the global stage 1 - Giordano, James (Henry Stewart Talks, 2023)
Data/cyber science and technology, Integrative Scientific Convergence, Volumes, velocities and vistas, Big data approaches and issues, Data acquisition and tracking, ‘Black box’ approach, Human looping and its implications